ANALISIS PERILAKU KEUANGAN DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA DI BATAM - Natalia, Erni Yanti; Arista, Anggia (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
According to the results of the 2020 population census, of the 2.06 million population in the Riau Islands, 71% of the population or around 1.45 million people are in the productive age range (15-64 years). The 2020 population census also shows that the population of the Riau Islands is still concentrated in Batam City, where around 57.95% of the population of the Riau Islands live in Batam City. Capital market investors in the Riau Islands are still very small compared to the number of productive age population, which indicates that the level of public awareness in investing is still low. This research aims to analyze the level of willingness of the millennial generation (in this case students) to invest. It is hoped that the results of this research will provide an overview of how financial behavior influences investment decisions; How does Financial Literacy influence Investment Decisions? The research method uses descriptive analysis with a quantitative approach. The population in this study consisted of students in the city of Batam. The sample for this research were students from the Accounting study program at Putera Batam University. The results of the research using the t test to test partial effects showed that: Financial Behavior influences Student Investment Decisions with a Sig value of 0.000<0.05; Financial Literacy influences student investment decisions with a Sig value of 0.000 <0.05. Meanwhile, by testing the influence simultaneously using the F test, it was found that Financial Behavior Financial Literacy jointly influences student investment decisions in Batam City with a Sig value of 0.000<0.05, where R Square shows 70.6%.